2021
DOI: 10.3390/pathogens10050609
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Similar Leptospira Serovars among Dog Keepers and Their Respective Dogs in Mwanza, Tanzania, the Need for a One Health Approach to Control Measures

Abstract: This study investigated seroepidemiology of Leptospira serovars among the dog keepers and their dogs in the city of Mwanza, Tanzania. A total of 205 dog keepers and 414 dogs were tested for Leptospira antibodies using a microscopic agglutination test (MAT). The median age of the dog keepers was 26 (inter quartile range (IQR): 17–40) years and median duration of keeping dogs was 36 (IQR: 24–120) months. The seropositivity of Leptospira antibodies was (33/205 (16.1%, 95% CI: 11.0–21.1) among dog keepers and (66/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In comparison with the observation made in a previous study which reported a prevalence of 38.0% in sheep in Morogoro, Tanzania [20], probably due to a small number of sheep in the Morogoro study areas, most of these animals are imported from the outside the island and are used as a source of meat consumption. In dogs, the results showed that 26.25% were seropositive Leptospira antibodies, the results are in agreement with the study by Msemwa et al [11] in Mwanza, Tanzania in which the seropositivity was 16.1%. This could be justified by the fact that this study included a cluster (farmers and livestock keepers) of a higher risk for Leptospira than those enrolled in the previous study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In comparison with the observation made in a previous study which reported a prevalence of 38.0% in sheep in Morogoro, Tanzania [20], probably due to a small number of sheep in the Morogoro study areas, most of these animals are imported from the outside the island and are used as a source of meat consumption. In dogs, the results showed that 26.25% were seropositive Leptospira antibodies, the results are in agreement with the study by Msemwa et al [11] in Mwanza, Tanzania in which the seropositivity was 16.1%. This could be justified by the fact that this study included a cluster (farmers and livestock keepers) of a higher risk for Leptospira than those enrolled in the previous study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it is estimated that Zanzibar has 8095 dogs, found in Kaskazini 'A' (1810), Kaskazini 'B' (476), Kusini (1080), Kati (1865), Magharibi 'A' (229), Magharibi 'B' (341), Micheweni (346), Wete (736), Chakechake (260) and Mkoani (952) [7]. Findings from previous studies from Tanzania have shown that leptospiral infection is very common in domesticated and wild animals, rats, shrews, and people in several regions of the country [2,[8][9][10][11]. Moreover, serovars circulating in Tanzania reported in rodents, shrews, and domestic animals were identified as Sokoine, Lora, Kenya, Grippotyphosa, Hebdomadis, Pomona, and Canicola [2].…”
Section: Introductionmentioning
confidence: 99%
“…Canine leptospirosis was also not associated with the owners’ educational and occupational backgrounds. Several studies have demonstrated that a higher education level significantly encouraged a positive attitude and better preventative practices towards leptospirosis as a zoonotic disease in humans [ 57 , 58 ]. Therefore, it may be logical to assume that a similar association also exists between an owner’s education level and attitude towards veterinary prevention against canine leptospirosis.…”
Section: Discussionmentioning
confidence: 99%